2013
DOI: 10.1002/qua.24594
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the pH-rate profile for dimethyl sulfide oxidation by hydrogen peroxide: The role of elusive H3 O2 + Ion

Abstract: Experimental kinetics of sulfide oxidation by hydrogen peroxide presents a pH-dependent profile. In this article, it was carried out a detailed study of the mechanism and kinetics of dimethyl sulfide (DMS) oxidation by H 2 O 2 in neutral, acid, and basic aqueous medium using ab initio calculations. The results point out that DMS oxidation in neutral aqueous medium occurs through its direct reaction with H 2 O 2 . In acid medium, cluster-continuum model calculations shows that H 3 O 1 ðH 2 O 2 Þ ðH 2 OÞ 2 clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The physical and chemical stimuli associated with re-submersion following air exposure could result in a burst of H 2 O 2 production. DMSO is the first product of the aqueous phase reaction between DMS and H 2 O 2 5152, so coincident release of H 2 O 2 could result in rapid oxidation of dissolved DMS to DMSO.…”
Section: Discussionmentioning
confidence: 99%
“…The physical and chemical stimuli associated with re-submersion following air exposure could result in a burst of H 2 O 2 production. DMSO is the first product of the aqueous phase reaction between DMS and H 2 O 2 5152, so coincident release of H 2 O 2 could result in rapid oxidation of dissolved DMS to DMSO.…”
Section: Discussionmentioning
confidence: 99%
“…As a final example, the hybrid cluster‐continuum approach was used to predict the pH‐rate profile for the oxidation of the dimethyl sulfide by hydrogen peroxide, using high level MP4/TZVPP+diff calculations on the CPCM/X3LYP/DZ+P(d)+diff optimized geometries, corresponding to the reaction: CH3SCH3+H2O2CH3normalS()=normalOCH3+H2normalO In acidic medium, the calculations have indicated that the “protonated” peroxide ion is better represented by the H 3 O + (H 2 O 2 )(H 2 O) 2 ionic cluster, because the proton stays bound to the water molecule. In the transition state, two water molecules are lost to form the most stable transition state.…”
Section: Applicationsmentioning
confidence: 99%
“…24,[33][34][35][36][37][38] In the cases that free ionic species are involved, the method is less reliable and may be needed to use hybrid clustercontinuum approaches. 39,40 In the application of continuum models for chemical reactions, it is important to take care about the type of reaction is being considered. Scheme 1 present some cases.…”
Section: Introductionmentioning
confidence: 99%